Mampukah Akad Syariah Menghindarkan Persoalan Riba - Muhammad Elsa Tomisa (LPPM ISNJ Bengkalis, 2014)
Banking world is a financial management agency for profit, based on those principles requires cooperation and the services offered, of the profits, will be used as a source of life support, in particular there are things that are forbidden, for the banking world especially issues of interest or usury, therefore, the bank which offers a system that is the subject of interest in Islamic Jurisprudence problem is a matter of interest (rents) bank. Because, in general, banking business purpose is to gain from trade credit. Banks give credit to outsiders by levying interest through credit payments (which amount is the greatert than the amount of credit). The difference is usually called interest payments, that is the bank's profits. In this issue, they modernist intellectuals and scholars have different opinions depending on their point of view. There was a party of those who forbid it because the banking interest is seen as usury. But another class of permit. Although the Quran has clearly forbidden usury, only if the banking practice of conventional now including usury or not, the answer is the only necessary appreciation of what ticked practice. Therefore, this paper will explain the actual contract shariah be to address the problem of usury if he is not in the practice of manipulation by a long way at conventional.